SPEECH-TO-TEXT: A SECURED REAL-TIME LANGUAGE TRANSLATION PLATFORM FOR STUDENTS (FUDMA JOURNAL OF SCIENCES, 2024)
In order to establish effective communication and understanding among students regardless of language background, there is need to develop a common platform that will support this motive. This necessity has led to the emergence of Speech-to-Text (S-to-T) translation framework that enabling students with diverse languages to communicate directly without relying on intermediaries. English has become the foremost lingua franca in Nigeria, spoken widely across various ethnic groups. However, this continuous use of English language has affected the subsistence of indigenous Nigerian languages, leading to many children growing up unable to speak their native language. In modern, civilized societies, speech remains a primary and essential means of communication, allowing individuals to express a range of ideas from their minds through organized words, phrases, and sentences that follow grammatical rules. This work, Speech-to-Text: A secure real-time language translation platform for students, translates speech to English and Yoruba languages during chat. It was developed using ASP.Net with C# as the base technology. The model was developed with CSS, Bootstrap, JQuery, and JavaScript, ensuring responsiveness, while a secure SQL Server database repository supports data storage. The software is structured using the Object-Oriented Methodology (OOM). This platform presents a user-friendly and intuitive web interface that allows students of both English and Yoruba speakers to easily access and interact with other in real-time thereby bridging the communication gap between them.
Keywords: Boostrap; Google Cloud Translation; JavaScript; Hypertext Markup Language; Speech- to-Text Translation